Potential of Group Discussion as a means of Developing Students ' Lifelong Learning Skills in Tanzanian Higher Education Institutions: Lecturers ' Perspectives - Mwaikokesya, Mpoki (Papers in Education and Development, 2016)
Institutions and governments across the globe have been invariably striving to promote the vision of lifelong learning for years now. In some institutions, the discourse on the development of graduates ' lifelong learning skills has been linked with debates about improving the quality of teaching and learning using collaborative and group learning approaches. However, despite the wide acceptance of the use of group discussion in higher learning institutions of teaching and learning to promote students ' lifelong learning capacity, there have been mixed feelings on the potential of group discussion for developing this capacity, especially in the face of challenges such as a shift in student demographics and the changing pattern of university admissions. The conviction of the majority of higher education institutions which use group discussion in teaching and learning is its potential for promoting students ' high quality learning. The purpose of this paper was to assess the function of group discussion in teaching and learning, and university lecturers ' views on groups ' potential for improving undergraduates' learning using a qualitative approach. Key words: Lifelong learning, self-directed learning, Group discussion, teaching and learning